Modalities or Surfaces: Postmodern Poetics and a Riddle - Tapper, Janne (Nordic Theatre Studies, 2014)
This article will examine the playing with aesthetical surfaces in postmodern theatre and how it reflects the poetics and the cultural logic of late capitalism. Surfaces are examined as aesthetic elements of the postmodern culture of the image. This culture is not neutral as it seems to reject the modern spiritual depth, for instance, sense of history and hermeneutic depth. The article examines the riddle concerning how the absence of these aspects of human thought in surfaces generates the spectators' need to produce coherent individual activities, trajectories, and eventually acoherent culture. This reflexive mechanism of surfacesis analyzed within the framework of Donald Norman's (2005) cognitive principles of design. Starting from the premise of Gilles Deleuze's and Felix Guattari's (1987) and Lev Vygotsky's (1978) notions of play, it is interpreted that postmodern stage and culture works, metaphorically, like the plane of immanence, the way of thinking in which an agent is able to move, make transitions and crossings in a revolutionary way without restrictions of reality's conditions. However, culturally the blurring of boundaries between play and reality may lead to delirium and ill-founded practices. Theatre and art examine these ill-founded practices but involve in their poetics a strong dimension of reflexive level of human cognition. This reflexive level is an explanatory perspective, which helps spectators examine theatre's mechanisms as metaphors of cultural logic, to achieve a critical position extrinsic from the flux of postmodern culture. This poetics is examined in several cases of theatrical representation including Sofia Coppola's film The Bling Ring (2013), The Need Company's production The Lobster Shop (2006), Kristian Smeds' production The Unknown Soldier (2007) and in several casesof postmodern art and stage design.